Virtual reality in K‐12 and higher education: A systematic review of the literature from 2000 to 2019. (16th March 2021) - Luo, Heng; Li, Gege; Feng, Qinna; Yang, Yuqin; Zuo, Mingzhang
Abstract: This study is a systematic review of 20 years of research on the usage of virtual reality (VR) in K‐12 and higher education settings, which aims to consolidate, evaluate, and communicate evidence that can inform both the theory and practice of VR‐based instruction. A total of 149 articles were selected from three major academic databases using search strings and manual screening protocols. The literature analysis emphasized four interrelated aspects of VR‐based instruction: instructional context, instructional design, technological affordances, and research findings. The results revealed evolving trends in the VR literature in terms of publication patterns, pedagogical assumptions, equipment usage, and research methodologies, as well as the contextual factors behind VR adoption in education. Additionally, a meta‐analysis was conducted to examine the efficacy of VR‐based instruction, with results indicating an overall medium effect and several moderating factors. Finally, practical implications and a future research agenda for VR‐based instruction are discussed. Lay Description: What is currently known about the subject matter: VR is a promising educational technology with several learning benefits. Research findings on VR‐based education have been conditional and inconclusive. Contemporary research on VR in K‐12 and higher education settings lacks a comprehensive review and meta‐analysis. What this paper adds: This paper systematically reviewed 20 years of empirical research on VR application in K‐12 and higher education. This paper revealed evolving trends in the VR literature in terms of publication patterns, pedagogical assumptions, and equipment usage. This paper synthesised the key pedagogical and technological features of VR interventions. This paper reported an overall medium effect size of VR‐based instruction and several moderating factors. Implications of this study for practitioners: Decision to adopt VR technology should be based on the careful assessment of learning domains and tasks. Embedded functions for learning assessment, collaboration, and data collection are recommended for future VR interventions. Research in VR is needed with focus on advanced technology, cross‐disciplinary comparison, holistic instructional process, and cost‐benefit analysis.